Principal Strategies In Implementing Promotion Management - Salsabila, Infra; Megawati, Megawati (JUPE : Jurnal Pendidikan Mandala, 2025)
Competition in the education sector is very tight, especially in the city of Tanjungpinang, where the development of Islamic-based schools is thriving. This research aims to find out how the strategy of the principal of SDIT Tunas Ilmu, one of the SDITs in Tanjungpinang, is implemented in educational promotion management. This study is qualitative research using descriptive methods. Data collection uses observation, interviews, and documentation, as well as data analysis through data reduction and drawing conclusions. The results of the study indicate that it has been effective. In accordance with the principles of management POAC.